Assertive Action in Indonesian Debate Competition 2019 - Lahunduitan, Tutike; Endry Boeriswati; Asti Purbarini (Universitas Pendidikan Ganesha, 2022)
Students must be directed to express themselves positively, especially in expressing opinions and ideas, because they have a wide range of positive potential and bright pictures that can be used as alternative suggestions, especially regarding the problems currently experienced by Indonesia. This study analyzes assertive speech acts, forms, and functions in the 2019 Indonesian Debate Competition. This research is descriptive qualitative research using content analysis methods. The research subject under study was a debate competition video with the data object in the form of utterances showing the structure of assertive speech acts. This study's data collection techniques and procedures are documentation, recordings, and transcripts. The technique used to analyze the data is descriptive qualitative analysis. The findings show that news sentences as assertive speech acts have the highest intensity at 77.85%, imperative sentences at 12.14%, and interrogative sentences at 10%. Then states as a function of influential speech acts, which has the highest power of 26.42%, shows 22.14%, informs 17.14%, suggests 10.71%, and confirms 10.71%. This research is recommended to add to the general public's insight as a consideration of teaching materials for assertive speech acts at the tertiary and secondary levels.